1993
DOI: 10.1021/ma00069a005
|View full text |Cite
|
Sign up to set email alerts
|

Water-induced crystalline transition of polyamide 66: a combined x-ray and molecular modeling approach

Abstract: Combined X-ray and molecular modeling approaches have been used to characterize and rationalize the crystalline transition displayed by polyamide 6,6 upon temperature and water treatment. Polyamide 6,6 material as processed by extrusion exhibits crystalline features close to those reported for the pseudohexagonal a2 phase. Upon storage, the water uptake induces solid state polymorphic transitions. This results in an evolution of the crystalline moiety toward the so-called ai triclinic form. This phenomenon is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 6 publications
1
19
2
Order By: Relevance
“…In fact, it has been shown that amorphous segments interact with the crystalline stems at the interface, preferentially with the bc plane (b being the chain axis). 113 Such a mechanism is consistent with the observation that the Brill transition occurs by point-by-point motion involving a small group of adjacent PA chains. This does not involve long-range cooperative motion of the entire crystal.…”
Section: Interaction Between Amorphous and Crystalline Domainssupporting
confidence: 87%
See 1 more Smart Citation
“…In fact, it has been shown that amorphous segments interact with the crystalline stems at the interface, preferentially with the bc plane (b being the chain axis). 113 Such a mechanism is consistent with the observation that the Brill transition occurs by point-by-point motion involving a small group of adjacent PA chains. This does not involve long-range cooperative motion of the entire crystal.…”
Section: Interaction Between Amorphous and Crystalline Domainssupporting
confidence: 87%
“…Water transforms the pseudohexagonal crystalline phase in PA-66 (not the high-temperature Brill phase) to a triclinic a phase. 113 Moisture that enables PA-6 to crystallize preferentially in the a-crystalline form at ambient temperatures 39,114 causes it to crystallize completely in the a form at high temperatures and even brings about transformation of the c form into the a form. 28,105,115 Because water (solvent) molecules diffuse preferentially into the amorphous regions, these data show that the interactions between the crystalline stems and amorphous segments are bidirectional; that is, an increase in the mobility of the amorphous chains can affect the motion of the crystalline stems.…”
Section: Interaction Between Amorphous and Crystalline Domainsmentioning
confidence: 99%
“…3 By dilatometric technique Kettle noted the glass-transition temperature Tg of nylon 6 as a function of water content decreased first sharply, then slowly with an increase in water content with plateau region (water content region 3-5 wt%). 4 The transition of ct2 to ct 1 crystal for nylon 66 by water has been reported by Vergelati et al 5 and the relaxation times (T 2 ) of water which penetrated into nylon 66 has been found to be shorter by three order of magnitude than that of bulk water by Fyfe et al 6 However, all the literature has ignored the effect of the balance of terminal groups which might facilitate the ionization of water penetrated in polyamide. Thus, in order to explain the phenomenological facts described above the hydrogen bonding in polyamide should be discussed in view of fN and the existing state of water in the polymer with different fN·…”
Section: Introductionmentioning
confidence: 90%
“…First, some recent advances in the understanding of the Brill transition will be discussed. It is almost certain now that crystallization of nylon 66 at the quiescent state or during processing (such as extrusion and spinning) in the melt always first produces the pseudohexagonal structure (Vergelati, Imberty & Prez, 1993;Ramesh, Keller & Eltink, 1994;Hsiao et al, 1995). The transformation to the conventional triclinic structure not only depends on the previous crystallization conditions but is also kinetically limited.…”
Section: Draw Ratio (A)mentioning
confidence: 99%